Implementasi Kebijakan Pengelolaan Sampah Berbasis Partisipasi Masyarakat: Studi Kasus Desa Teteaji Kabupaten Sidenreng Rappang - Nur Annisa; Erfina Erfina; Muhammad Nur (Yayasan Literasi Sains Indonesia, 2026)
The waste problem in rural areas is a serious challenge due to the increasing volume of waste and the limitations of the management system. Population growth is always followed by an increase in waste volume, thus demanding changes in waste management, especially from the old paradigm (collect, transport, dispose) to the new paradigm with the 3R concept (reduce, reuse, recycle). This study aims to analyze the implementation of community participation-based waste management policies in Teteaji Village, Sidenreng Rappang Regency. This study is based on Merilee S. Grindle's policy implementation theory, namely Content of Policy and Context of Implementation, using a qualitative approach with data collected through interviews, observation, and documentation. Data analysis was carried out using Nvivo 12 Plus software for coding, thematic analysis, and data visualization. The results of the study indicate that the implementation of policies in waste management has not been running optimally, characterized by the absence of village regulations as an operational basis, limited facilities and infrastructure, and weak coordination between actors. Community participation is quite good, but is still incidental and not systematically organized. Therefore, the success of policy implementation is influenced by the interaction between the policy content and the implementation context, so that strengthening of regulations, facilities and infrastructure, and an integrated management system is required to realize sustainable waste management.